Tau excess impairs mitosis and kinesin-5 function, leading to aneuploidy and cell death - Anne-Laure Bougé; Marie-Laure Parmentier (The Company of Biologists, 2016)
In neurodegenerative diseases such as Alzheimer's disease (AD), cell cycle defects and associated aneuploidy have been described. However, the importance of these defects in the physiopathology of AD and the underlying mechanistic processes are largely unknown, in particular with respect to the microtubule (MT)-binding protein Tau, which is found in excess in the brain and cerebrospinal fluid of affected individuals. Although it has long been known that Tau is phosphorylated during mitosis to generate a lower affinity for MTs, there is, to our knowledge, no indication that an excess of this protein could affect mitosis. Here, we studied the effect of an excess of human Tau (hTau) protein on cell mitosis in vivo. Using the Drosophila developing wing disc epithelium as a model, we show that an excess of hTau induces a mitotic arrest, with the presence of monopolar spindles. This mitotic defect leads to aneuploidy and apoptotic cell death. We studied the mechanism of action of hTau and found that the MT-binding domain of hTau is responsible for these defects. We also demonstrate that the effects of hTau occur via the inhibition of the function of the kinesin Klp61F, the Drosophila homologue of kinesin-5 (also called Eg5 or KIF11). We finally show that this deleterious effect of hTau is also found in other Drosophila cell types (neuroblasts) and tissues (the developing eye disc), as well as in human HeLa cells. By demonstrating that MT-bound Tau inhibits the Eg5 kinesin and cell mitosis, our work provides a new framework to consider the role of Tau in neurodegenerative diseases.